2022
DOI: 10.3390/genes13061007
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Genetic Diversity of Chinese Honeybee (Apis Cerana Cerana) in Central China

Abstract: Central China has a rich terrain with a temperate monsoon climate and varied natural environments for the Chinese honeybee (Apis cerana cerana). However, little comprehensive research on population genetic diversity has been done in this area. A population survey of the structure and genetic diversity of Apis cerana cerana in this area is deeply needed for understanding adaptation to variable environments and providing more references for the protection of honeybee biodiversity. In this study, we present a dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…Our data showed that the average paired F ST value of the 12 populations was 0.0182 (Table 2). The level of genetic differentiation was lower than estimates in the Tibetan Plateau region (mean F ST = 0.0758) (Tang et al, 2022) and North China (mean F ST = 0.132) (Yancan et al, 2019) and was similar to estimates in Central China (mean F ST = 0.02470) (Fang et al, 2022) and Yunnan (mean F ST = 0.027) (Montero-Mendieta et al, 2019). The mean F ST value between the eastern and western populations was 0.0218, which was higher than the overall mean (0.0182), indicating that there was a certain degree of genetic differentiation between the two geographic regions (Table 2; Figure 3).…”
Section: Population Genetic Differentiationsupporting
confidence: 44%
See 2 more Smart Citations
“…Our data showed that the average paired F ST value of the 12 populations was 0.0182 (Table 2). The level of genetic differentiation was lower than estimates in the Tibetan Plateau region (mean F ST = 0.0758) (Tang et al, 2022) and North China (mean F ST = 0.132) (Yancan et al, 2019) and was similar to estimates in Central China (mean F ST = 0.02470) (Fang et al, 2022) and Yunnan (mean F ST = 0.027) (Montero-Mendieta et al, 2019). The mean F ST value between the eastern and western populations was 0.0218, which was higher than the overall mean (0.0182), indicating that there was a certain degree of genetic differentiation between the two geographic regions (Table 2; Figure 3).…”
Section: Population Genetic Differentiationsupporting
confidence: 44%
“…Populations in different environments face different selection pressures. Elevation is an important environmental parameter; populations at higher elevations must adapt to various factors, such as higher radiation, lower temperatures, precipitation, and differences in plant phenological periods than those at lower elevations (Montero-Mendieta et al, 2019;Fang et al, 2022;Chen and Luo, 2023). The Guizhou region shows a gradual elevation from east to west and does not have features associated with geographic isolation, such as obvious islands and steep mountain ranges (Zhou et al, 2023).…”
Section: Population Genetic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of pairwise heterozygosity values led us to conclude that genetic differentiation between populations is low. Earlier studies on A. cerana have also reported low genetic differentiation between different regional populations (Xu et al, 2013;Fang et al, 2022).…”
Section: Genetic Diversity and Differentiation Of Populationsmentioning
confidence: 83%
“…Combined with H o < H e , there was a certain degree of inbreeding. The F ST value has three levels of different genetic differentiation: moderate differentiation was 0.05 to 0.15, larger differentiation was 0.15 to 0.25 and high differentiation was greater than 0.25 [ 27 ]. In fact, RAD-seq has the drawbacks that missing data tends to inflate estimates of F ST [ 17 ].…”
Section: Discussionmentioning
confidence: 99%